Gaps in Financial Inclusion in fruit production in Boyacá, Colombia - Niño-Amézquita, Daniela; Sánchez-Rueda, Norlando (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Financial Inclusion (FI) implies bringing the financial sector closer to the entire population in order to improve their living conditions. However, its reach in the rural sector is limited. In view of this, this research identifies gaps in FI focusing on access, use and quality of financial products and services in the context of fruit production in the department of Boyacá, Colombia. For this purpose, a qualitative analysis was carried out among regional financial sector providers and representatives of the fruit association Asohofrucol, Boyacá. The findings show that the lack of financial guarantees, technological resources, informality, physical distance, poor financial literacy and diversity of financial products are the main gaps in FI. Based on these results, alternatives for the mitigation of gaps are consolidated, highlighting the articulation between institutions and rural communities to effectively address problems.